Pengembangan Sistem Manajemen Inventaris Aset Berbasis Qr Code dengan Pendekatan Agile Development pada Diskominfo Kabupaten Tegal - Muzaqi, Achmad Fatich; Aang Alim Murtopo; Zaenul Arif (Institut Teknologi dan Bisnis (ITB) Semarang, 2026)
Asset inventory management is vital for enhancing the operational efficiency of an organization. At the Communication and Informatics Office of Tegal Regency, the process for managing asset inventory is still performed manually, leading to various issues including challenges in asset documentation, data retrieval, management of borrowing, reporting damage, and overseeing the condition of assets. This research intends to create a web-based asset inventory management solution that leverages Quick Response (QR) Code technology to boost the effectiveness, efficiency, and precision of inventory management. The methodology employed for the system's development was Agile Development, which includes stages such as planning, analyzing requirements, designing the system, developing, testing, and conducting iterative evaluations. Data gathering was conducted through observation, interviews, and reviewing existing literature. The completed system offers several key features, such as inventory management, the ability to generate and scan QR Codes, processes for borrowing and returning assets, damage reporting, a monitoring dashboard, and management of user access based on roles. The findings reveal that the implemented system enhances asset identification through QR Codes, delivers real-time inventory data, and enables more efficient monitoring of assets. According to Black Box Testing results, all functionalities of the system performed in alignment with the identified functional requirements. Consequently, the web-based asset inventory management system utilizing QR Code technology can act as a useful solution to enhance the asset inventory management quality at the Communication and Informatics Office of Tegal Regency.